Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 1, b = 6, c = 5


= 1.5 = 5


And either of their sum or difference = b


= 6


Thus the two terms are 1 and 5


Sum = 5 + 1 = 6


Product = 5.1 = 5




x(x + 1) + 5(x + 1) = 0


(x + 1)(x + 5) = 0


(x + 1) = 0 or (x + 5) = 0


x = -1, x = -5


Roots of equation are - 1, - 5


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics